2014
DOI: 10.1371/journal.pone.0108914
|View full text |Cite
|
Sign up to set email alerts
|

Spred-2 Deficiency Exacerbates Lipopolysaccharide-Induced Acute Lung Inflammation in Mice

Abstract: BackgroundAcute respiratory distress syndrome (ARDS) is a severe and life-threatening acute lung injury (ALI) that is caused by noxious stimuli and pathogens. ALI is characterized by marked acute inflammation with elevated alveolar cytokine levels. Mitogen-activated protein kinase (MAPK) pathways are involved in cytokine production, but the mechanisms that regulate these pathways remain poorly characterized. Here, we focused on the role of Sprouty-related EVH1-domain-containing protein (Spred)-2, a negative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 38 publications
6
33
0
Order By: Relevance
“…There was no significant difference in the levels of MEK2 between the groups (Figure 1, A and B), and there was no significant difference in the total number of alveolar macrophages recovered from Mek1 fl and Mek1 fl LysM Cre mice ( Figure 1C). We predicted that loss of MEK1 would decrease the macrophage proinflammatory response to LPS stimulation, which would be consistent with results demonstrated by use of pharmacological MEK1/2 inhibitor compounds (19). To test this hypothesis, we stimulated alveolar macrophages ex vivo with LPS for 4 hours and measured proinflammatory gene expression.…”
Section: Resultssupporting
confidence: 76%
“…There was no significant difference in the levels of MEK2 between the groups (Figure 1, A and B), and there was no significant difference in the total number of alveolar macrophages recovered from Mek1 fl and Mek1 fl LysM Cre mice ( Figure 1C). We predicted that loss of MEK1 would decrease the macrophage proinflammatory response to LPS stimulation, which would be consistent with results demonstrated by use of pharmacological MEK1/2 inhibitor compounds (19). To test this hypothesis, we stimulated alveolar macrophages ex vivo with LPS for 4 hours and measured proinflammatory gene expression.…”
Section: Resultssupporting
confidence: 76%
“…Particularly, in DSS-induced colitis, bacteria that translocated to the mucosa interact with mucosal cells, such as macrophages, via toll-like receptors and promote the production of pro-inflammatory cytokines, resulting in overwhelming inflammatory responses48. We previously reported that Spred2-deficiency increased the production of pro-inflammatory cytokines by LPS-activated alveolar macrophages, and exacerbated LPS-induced lung injury59. In this study, however, the inflammatory response in the colonic mucosa of Spred2 mice was milder than WT mice, and only a small number of leukocytes infiltrated the mucosa of Spred2 KO mice; thus, the effect of Spred2-deficiency on macrophages cannot explain the decreased inflammatory responses detected in the colon of Spred2 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Their activation became only apparent in LPS-stimulated cultures, and men showed highly significant activation while women showed only a trend. Similarly, the central protective gene IL-6, the tumorigenesis controlling gene HIVEP1[25], and SPRED2 [26] which are all clearly anti-inflammatory in their effects were significantly more highly expressed in men than women.…”
Section: Discussionmentioning
confidence: 99%